2003
DOI: 10.1007/s003800300011
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical regional myocardial uptake between 201Thallium and 123I-BMIPP SPECT in patients with cardiomyopathy

Abstract: The clinical significance of the paradoxical mismatched phenomenon between (201)Tl and (123)I-BMIPP is still unknown. We report two cases that revealed paradoxical regional myocardial uptake between two tracers in patients with cardiomyopathy. There may be abnormal myocardium in these patients where active transportation of (201)Tl is disturbed and passive transportation of (123)I-BMIPP is not disordered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…With regard to HCM, a significant acceleration in the regional myocardial washout rate in the thickened part as well as the non-thickened part was reported in the 1990s 9 . That study showed normal uptake in the inferior wall that had no thickening in two HCM patients with 123 I-labeled 15-p-iodophenyl -3R,S-methyl pentadecanoic acid 123 I-BMIPP , and reduced uptake in both the early phase and the late phase with 201 Tl, suggesting the possibility of myocardial damage in the non-thickened part 10 . Sugihara et al 11 also found that just as RR was observed in 81.8 of HCM patients by imaging in 30 minutes and 180 minutes after stress with the 99mTc-labeled agent, RR also often appeared in the anterior wall, posterior wall, and a part of the septum.…”
Section: Discussionmentioning
confidence: 90%
“…With regard to HCM, a significant acceleration in the regional myocardial washout rate in the thickened part as well as the non-thickened part was reported in the 1990s 9 . That study showed normal uptake in the inferior wall that had no thickening in two HCM patients with 123 I-labeled 15-p-iodophenyl -3R,S-methyl pentadecanoic acid 123 I-BMIPP , and reduced uptake in both the early phase and the late phase with 201 Tl, suggesting the possibility of myocardial damage in the non-thickened part 10 . Sugihara et al 11 also found that just as RR was observed in 81.8 of HCM patients by imaging in 30 minutes and 180 minutes after stress with the 99mTc-labeled agent, RR also often appeared in the anterior wall, posterior wall, and a part of the septum.…”
Section: Discussionmentioning
confidence: 90%
“…In this case, the uptake of the I-123 BMIPP tracer was greater in the initial images than that of Tl-201. This phenomenon is called paradoxical mismatch and considered to result from an artifact, especially when observed in the inferior wall due to attenuation and infra diaphragmatic scatter [ 14 ]. This is also observed in the non-hypertrophied regions of patients with hypertrophic cardiomyopathy [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is called paradoxical mismatch and considered to result from an artifact, especially when observed in the inferior wall due to attenuation and infra diaphragmatic scatter [ 14 ]. This is also observed in the non-hypertrophied regions of patients with hypertrophic cardiomyopathy [ 15 ]. Both conditions are less likely to explain the paradoxical mismatch between I-123 BMIPP and Tl-201 observed in the current case.…”
Section: Discussionmentioning
confidence: 99%
“…Yamabe et al [3] identified reduced BMIPP uptake in stenosis-related myocardial territory in 50% of patients with stable angina. A mismatch between TL and BMIPP uptake reflects damaged, but viable regions exposed to ischemia in patients with coronary heart disease [4]. Therefore, TL and BMIPP dual SPECT (d-SPECT) might be useful to detect myocardial ischemia at rest.…”
Section: Introductionmentioning
confidence: 99%